2020
DOI: 10.1162/evco_a_00267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Programming Hyper-Heuristics with Vehicle Collaboration for Uncertain Capacitated Arc Routing Problems

Abstract: Due to its direct relevance to post-disaster operations, meter reading and civil refuse collection, the Uncertain Capacitated Arc Routing Problem (UCARP) is an important optimisation problem. Stochastic models are critical to study as they more accurately represent the real-world than their deterministic counterparts. Although there have been extensive studies in solving routing problems under uncertainty, very few have considered UCARP, and none consider collaboration between vehicles to handle the negative e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Chen et al [20] studied the average run time of solving some CARP-SSTT instances optimally, while the run time of finding e-optimal solutions is studied in [7]. Instead of the run time of (approximately) solving UCARP instances, Maclachlan et al [28] reported the computational time for training routing policies.…”
Section: G Computation Timementioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al [20] studied the average run time of solving some CARP-SSTT instances optimally, while the run time of finding e-optimal solutions is studied in [7]. Instead of the run time of (approximately) solving UCARP instances, Maclachlan et al [28] reported the computational time for training routing policies.…”
Section: G Computation Timementioning
confidence: 99%
“…This assumption is not always true in reality. To the best of our knowledge, MacLachlan et al [28] were the first to split deliveries in UCARP and proposed an enhanced GPHH with vehicle collaboration (GPHH-C). The vehicle collaboration was proved to be effective compared to the GPHH without collaboration [25] on the ugdb, uval, uegl benchmarks, and also to EDASLS [17] on most of the tested instances.…”
Section: Robust Optimisation In Carp With Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both profits and travel times are considered to be stochastic. The CARP with uncertain demands is also addressed by MacLachlan et al [151], but in this case vehicles can collaborate to handle the negative effects of uncertainty. It seems that, even if uncertainty has been extensively studied for the CARP, only some recent papers have taken into account this feature in other ARPs, so this is something that could be addressed in future works.…”
Section: Stochastic Datamentioning
confidence: 99%